Multi-layer mucilage of Plantago ovata seeds: Rheological differences arise from variations in arabinoxylan side chains. (1st June 2017) - Yu, Long; Yakubov, Gleb E.; Zeng, Wei; Xing, Xiaohui; Stenson, John; Bulone, Vincent; Stokes, Jason R.
Graphical abstract: Highlights: A three layered structure in Plantago ovata seed mucilage has been discovered. Major constituent arabinoxylans in each layer were isolated by step-wise extraction. Distinct polymer conformations were found in the structures with similar branching. Small differences in fine structure lead to substantial rheological differences. Abstract: Mucilages are hydrocolloid solutions produced by plants for a variety of functions, including the creation of a water-holding barrier around seeds. Here we report our discovery of the formation of three distinct mucilage layers around Plantago ovata seeds upon their hydration. Each layer is dominated by different arabinoxylans (AXs). These AXs are unusual because they are highly branched and contain β-1, 3-linked xylose in their side chains. We show that these AXs have similar monosaccharide and linkage composition, but vary in their polymer conformation. They also exhibit distinct rheological properties in aqueous solution, despite analytical techniques including NMR showing little difference between them. Using enzymatic hydrolysis and chaotropic solvents, we reveal that hydrogen bonding and side chain distribution are key factors underpinning the distinct rheological properties of these complex AXs.